Unity in diversity: The view from the (UAE) classroom. (22nd May 2012) - Nickerson, Catherine
Abstract : This talk is about finding 'unity in diversity'. I ask how we can best focus our research efforts and then design our teaching for those of us involved with teaching language for specific business purposes in the Asia Pacific region and the Middle East. In parts 1 and 2 of the presentation I discuss how we need to (i) refer to empirical evidence as the basis for our teaching and training materials, (ii) become more aware of the challenges posed by globalisation, (iii) understand the role played for business people by English as a lingua franca, alongside other languages and (iv) develop closer ties with people working in business and industry. In part 3 I discuss, first, a teaching project involving undergraduate research that is a course for our senior business students on workplace communication and, second, the development of an evaluation instrument to chart our students' progress in terms not only of their language proficiency but also their communication knowledge and skills.